Analisis Keputusan Orang Tua Dalam Pemilihan Pendidikan Anak Usia Dini di PAUD Terpadu Ummi Kecamatan Muara Bulian - Mariatul Kubro Khoiri Naya; Nyimas Muazzomi; Kasmiati . (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This research is motivated by the increasing number of parents who send their children to the Ummi Integrated PAUD in Muara Bulian District, including parents who live in Sungai Buluh Village, even though the school distance is relatively further and the cost of education is higher than PAUD in the neighborhood where the parents live. This phenomenon raises questions about the factors that influence parents' decisions in choosing early childhood education institutions. This study aims to determine the decisions of parents in choosing early childhood education in Ummi Integrated PAUD. The focus of this study is to find out what factors most influence parents' decisions in choosing early childhood education in Ummi Integrated PAUD, then to determine what factors and reasons influence the decisions of parents in Sungai Buluh Village in choosing Ummi Integrated PAUD as early childhood education. The research method used in this study is a mixed method model Sequential Explanatory design, namely research will be examined using data in the form of numbers and presented using words and language. In the first stage, data collection and quantitative data analysis were carried out using a questionnaire, then followed by qualitative analysis data collection in the second stage which was described qualitatively using words. The sample in this study was all parents who send their children to Ummi Integrated PAUD, totaling 68 parents and interviews with 7 parents who live in Sungai Buluh Village. The quantitative data analysis technique used the calculation of the average score value while the qualitative data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the questionnaire study showed that the factor that most influenced parents' decisions was the school's physical facilities with an average score of 2.58%. The next factor was the educator's profile with a score of 2.56%. In addition, the portion of religious education was also an important consideration with a score of 2.52%. The results of the interview study showed that parents' decisions in choosing early childhood education at Ummi Integrated PAUD were influenced by factors (1) school physical facilities, (2) educator profile, (3) portion of religious education, (4) costs, (5) location, (6) school vision and mission.